Mobile-Based Marketing Application for Coffee Beans and Ground Coffee at Andatu Store - Mifta Janatun Khonaza; Yuli Asriningtias (Engineering And Technology Journal, 2024)
Andatu Store, located in Danau Rata Village, Kisam Tinggi District, Ogan Komering Ulu Selatan Regency, is a single store that sells coffee beans and ground coffee from various selected types. Andatu Store faces several challenges related to the manual marketing process, which is detrimental to product quality. These challenges arise in the areas of coffee beans and ground coffee. The process of handling coffee beans and ground coffee is still mostly done manually, which may result in data loss and incorrect recording. Furthermore, stock monitoring at Andatu Store is still mostly done manually, contributing to delayed decision-making and inaccurate sales recapitulations. All these problems highlight the need for information technology solutions to improve efficiency and accuracy in the selling process, enable real-time stock monitoring, and facilitate communication between Sellers and buyers.